Aflasafe TZ01 and Aflasafe TZ02 for Tanzania - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
A to Z Textile Mills Ltd. signed a Technology Transfer and Licensing Agreement with IITA, obtaining the license to manufacture and distribute the Aflasafe TZ01 product. The manufacturing plant was completed in Arusha in November and had distributed enough Aflasafe to cover 40 hectares by the end of 2019.